# Formulae for two weighted binomial identities with the falling factorials

N/A
N/A
Protected

Share "Formulae for two weighted binomial identities with the falling factorials"

Copied!
8
0
0

Yükleniyor.... (view fulltext now)

Tam metin

(1)

FORMULÆ FOR TWO WEIGHTED BINOMIAL IDENTITIES WITH THE FALLING FACTORIALS

EMRAH KILIC¸ , NES¸E ¨OM ¨UR, AND SIBEL KOPARAL

Abstract. In this paper, we will give closed formulæ for weighted and alternating weighted binomial sums with the generalized Fi-bonacci and Lucas numbers including both falling factorials and pow-ers of indices. Furthermore we will derive closed formulæ for weighted binomial sums including odd powers of the generalized Fibonacci and Lucas numbers.

1. Introduction

For n > 1, define the generalized Fibonacci and Lucas sequences {Un}

and {Vn} by

Un= pUn−1− Un−2and Vn= pVn−1− Vn−2,

with U0= 0, U1= 1, and V0= 2, V1= p, respectively. The Binet formulæ

are Un = αn− βn α − β and Vn= α n+ βn, where α, β =p ±pp2− 4/2.

From [2], recall that for k ≥ 0 and n > 1,

Ukn= VkUk(n−1)− Uk(n−2) and Vkn= VkVk(n−1)− Vk(n−2).

As generalizations of the results of [9], Prodinger [8] derived a general formula for the sum

n

X

i=1

F2i+δ2m+ε,

where ε, δ ∈ {0, 1} , as well as for the corresponding sums for Lucas num-bers.

2000 Mathematics Subject Classification. 05A19, 11B37, 11B39.

Key words and phrases. Binary linear recurrences, binomial sums, closed formula, operator.

(2)

After this Kılı¸c et. al [4] derived general formulæ for the alternating sums n X i=1 (−1)iF2i+δ2m+ε and n X i=1 (−1)iL2m+ε2i+δ . Khan and Kwong [7] studied the sums

n X i=0 n i  imUi and n X i=0 n i  (−1)iimUi.

In [5], the authors computed alternating binomial sums

n X i=0 n i  (−1)if (n, i, k, t) and n X i=0 n i  g(n, i, k, t),

where f (n, i, k, t) and g (n, i, k, t) are certain products of generalized Fi-bonacci and Lucas numbers.

Kılı¸c et. al [3] computed the sums

n X i=0 n i  isUki2s+ε, n X i=0 n i  isVki2s+ε,

as well as their alternating analogues for positive integers k and s where ε is defined as before.

By inspiring from [3, 5], the authors [6] derived formulæ for the binomial sums n X i=0 n i  im(−1)if (n, i, k, t),

where f (n, i, k, t) is defined as before and m is a nonnegative integer and xm stands for the falling factorial defined by xm= x (x − 1) . . . (x − m + 1) .

In this paper, we compute the weighted binomial sums

n X i=0 n i  is+mg(i, k) and n X i=0 n i  (−1)iis+mg(i, k), where g(i, k) is either Uki2s+1or Vki2s+1for k, m > 0.

2. The Main results

Before our main results, we give some auxiliary results. For n ≥ 2, define the sequences {Xkn} , {Ykn} , {Wkn} and {Zkn} as

X0= 0, Xk= Uk, Xkn= (Vk+ 2) Xk(n−1)− Xk(n−2) ,

Y0= 0, Yk = Uk, Ykn= (Vk− 2) Yk(n−1)+ Yk(n−2) ,

W0= 2, Wk = Vk+ 2, Wkn= (Vk+ 2) Wk(n−1)− Wk(n−2) ,

(3)

The Binet formulæ are Xkn = 1 + αkn − 1 + βkn α − β , Ykn= αk− 1n − βk− 1n α − β , Wkn = 1 + αk n + 1 + βkn and Zkn= αk− 1 n + βk− 1n , where αk, βk =Vk±pVk2− 4  /2.

From (see Eq. (1.118) on page 36, [1]), we recall the following lemma: Lemma 1 ([1]). For nonnegative integers n and m,

n X i=0 n i  imai = amnm(1 + a)n−m[a 6= −1 and m 6= n] . We need the following result.

Theorem 1. For nonnegative integers n and m,

n X i=0 n i  imUki= nm (2 + Vk) mXk(n+m), n X i=0 n i  i1+mUki= nm (2 + Vk) m nXk(n+m)+ (m − n)Xk(n+m−1) , n X i=0 n i  (−1)iimUki= (−1) n+m nm (2 − Vk)m Yk(n+m), n X i=0 n i  (−1)ii1+mUki= nm(−1)n+m−1 (2 − Vk) m (m − n) Yk(n+m−1)− nYk(n+m) . Proof. Consider n X i=0 n i  imUki= 1 α − β " n X i=0 n i  imαki− n X i=0 n i  imβki # , which, by Lemma 1, equals

nm α − β " 1 + αkn (1 + βk)m − 1 + βkn (1 + αk)m # = n m (2 + Vk) mXk(n+m),

as claimed. One can easily obtain the rest of claimed identities.  Similar to the proof of Theorem 1, we have the following result without proof.

Theorem 2. For nonnegative integers n and m,

n X i=0 n i  imVki= nm (2 + Vk) mWk(n+m),

(4)

n X i=0 n i  i1+mVki= nm (2 + Vk) m(m − n)Wk(n+m−1)+ nWk(n+m) , n X i=0 n i  (−1)iimVki= (−1) n+m nm (2 − Vk) mZk(n+m), n X i=0 n i  (−1)ii1+mVki= nm(−1)n+m−1 (2 − Vk) m (m − n)Zk(n+m−1)− nZk(n+m) .

In order to generalize Theorems 1 and 2, we will define two new opera-tors. For n ≥ 1, define the operators DU and ∆U on Xk(n+m) and Yk(n+m)

as follows

DU Xk(n+m) = nXk(n+m)+ (m − n)Xk(n+m−1), (2.1)

∆U Yk(n+m) = nYk(n+m)− (m − n)Yk(n+m−1). (2.2)

For example, from Theorem 1 and (2.1), we have

n X i=0 n i  i2+mUki= DU " n X i=0 n i  im+1Uki # = DU  nm (2 + Vk) m nXk(n+m)+ (m − n)Xk(n+m−1)   = n m (2 + Vk) mn2Xk(n+m)+ (m − n)(2n − 1)Xk(n+m−1) +(m − n)(m − n + 1)Xk(n+m−2) .

From the discussion above, if

n P i=0 n ii s−1+mU kiis of the form n m (2+Vk)m P t≥0 atXt, then n X i=0 n i  is+mUki= nm (2 + Vk) mDU   X t≥0 atXt  .

Hence the coefficients atcan be computed iteratively. Iterative process is

summarized in the theorem:

Theorem 3. The polynomials as,r(m, n) satisfy the recurrence

as,r(m, n) = (n − r)as−1,r(m, n) + (m − n + r − 1)as−1,r−1(m, n), s ≥ 1,

where the initial value a0,0(m, n) = 1 and if r < 0 or r > s, as,r(m, n) = 0.

For any integers m, s ≥ 0, i) n X i=0 n i  is+mUki= nm (2 + Vk)m s X r=0 as,r(m, n)Xk(n+m−r), (2.3)

(5)

ii) n X i=0 n i  (−1)iis+mUki= nm(−1)n+m (2 − Vk)m s X r=0 (−1)ras,r(m, n)Yk(n+m−r). (2.4) Proof. i) Recall that

n X i=0 n i  is+mUki= DU n X i=0 n i  is−1+mUki ! . Thus by (2.1), we have s X r=0 as,r(m, n)Xk(n+m−r)= DU "s−1 X r=0 as−1,r(m, n)Xk(n+m−r) # = s−1 X r=0 as−1,r(m, n) (n − r)Xk(n+m−r)+ (m − n + r)Xk(n+m−r−1)  = nas−1,0(m, n)Xk(n+m)+ s−1 X r=1 (n − r)as−1,r(m, n)Xk(n+m−r) + s−1 X r=1 (m − n + r − 1)as−1,r−1(m, n)Xk(n+m−r) + (m − n + s − 1)as−1,s−1(m, n)Xk(n+m−s) = nas−1,0(m, n)Xk(n+m)+ (m − n + s − 1)as−1,s−1(m, n)Xk(n+m−s) + s−1 X r=1 ((n − r)as−1,r(m, n) + (m − n + r − 1)as−1,r−1(m, n)) Xk(n+m−r). Since as−1,r(m, n) = 0 if r < 0 or r > s − 1, we write s X r=0 as,r(m, n)Xk(n+m−r) = s X r=0 [(n − r)as−1,r(m, n) + (m − n + r − 1)as−1,r−1(m, n)] Xk(n+m−r).

The recurrence of as,r(m, n) follows by comparing coefficients.

ii) Observing n X i=0 n i  (−1)iis+mUki= ∆U " n X i=0 n i  (−1)iis−1+mUki # ,

(6)

For n ≥ 1, define the operators DU and ∆U on Wk(n+m) and Zk(n+m) as DV Wk(n+m) = nWk(n+m)+ (m − n)Wk(n+m−1), ∆V Zk(n+m) = nZk(n+m)− (m − n)Zk(n+m−1). Theorem 4. For m, s ≥ 0, n X i=0 n i  is+mVki= nm (2 + Vk)m s X r=0 as,r(m, n)Wk(n+m−r), (2.5) n X i=0 n i  (−1)iis+mVki= nm(−1)n+m (2 − Vk)m s X r=0 (−1)ras,r(m, n)Zk(n+m−r). (2.6) Proof. The proof is similar to the proof of Theorem 3. 

3. Additional Sums Formulæ including odd powers of the Generalized Fibonacci and Lucas numbers

In this section, we will derive much more general case of the results of Theorems 3 and 4 by taking odd powers of the generalized Fibonacci and Lucas numbers. Before this, we need to recall some facts.

From [10], for reals m and n, recall that

(m + n)k = (k−1)/2 X i=0 k i 

(mn)i(mk−2i+ nk−2i) if k is odd, and (m − n)k= (k−1)/2 X i=0 k i 

(−1)i(mn)i(mk−2i− nk−2i) if k is odd. (3.1)

Now we are ready to give our first claim: Theorem 5. For k, s > 0, n X i=0 n i  is+mUki2s+1= n mU2s k (V2 k − 4)s s X j=0 (−1)j2s + 1 j  1 (2 + Vk(2s−2j+1))m × s X r=0 as,r(m, n)Xk(2s−2j+1)(n+m−r).

Proof. For k > 0, by the Binet formula of {Un} and (3.1), we have n X i=0 n i  is+mUki2s+1= n X i=0 n i  is+m α ki− βki α − β 2s+1

(7)

= 1 (α − β)2s+1 n X i=0 n i  is+m × s X j=0 2s + 1 j  (−1)jαki(2s−2j+1)− βki(2s−2j+1) = 1 (p2− 4)s s X j=0 2s + 1 j  (−1)j n X i=0 n i  is+mUki(2s−2j+1),

which, by taking k(2s + 1 − 2j) replace of k in (2.3), equals

nmU2s k (V2 k−4) s s X j=0 2s + 1 j  (−1)j 2 + Vk(2s−2j+1) m s X r=0 as,r(m, n)Xk(2s−2j+1)(n+m−r), as claimed.  Theorem 6. For k, s > 0, n X i=0 n i  (−1)iis+mUki2s+1 = (−1)n+m n mU2s k (V2 k − 4)s s X j=0 (−1)j2s + 1 j  1 (2 − Vk(2s−2j+1))m × s X r=0 (−1)ras,r(m, n)Yk(2s−2j+1)(n+m−r).

Proof. For k > 0, consider

n X i=0 n i  (−1)iis+mUki2s+1= n X i=0 n i  (−1)iis+m α ki− βki α − β 2s+1 , which, by (3.1), equals n X i=0 n i  (−1)iis+m   s X j=0 2s + 1 j  (−1)j α ki(2s−2j+1)− βki(2s−2j+1) (α − β)2s+1 !  = 1 (p2− 4)s s X j=0 2s + 1 j  (−1)j n X i=0 n i  (−1)iis+mUki(2s−2j+1).

By taking k(2s + 1 − 2j) instead of k in (2.4), the claimed result follows.  Using (2.5) and (2.6), and, by following the proof of Theorem 5, we have the following result without proof.

(8)

n X i=0 n i  is+mVki2s+1= nm s X j=0 2s + 1 j  1 2 + Vk(2s−2j+1) m × s X r=0 as,r(m, n)Wk(2s−2j+1)(n+m−r). Theorem 8. For k, s > 0, n X i=0 n i  (−1)iis+mVki2s+1= (−1)n+mnm × s X j=0 2s + 1 j  1 2 − Vk(2s−2j+1) m s X r=0 (−1)ras,r(m, n)Zk(2s−2j+1)(n+m−r). ACKNOWLEDGEMENTS

The authors would like to thank the referee for carefully reading the paper and for giving a number of helpful suggestions.

References

[1] H. W. Gould, Combinatorial Identities, Morgantown, W. Va., 1972.

[2] E. Kılı¸c and P.Stanica, Factorizations and representations of second order linear recurrences with indices in arithmetic progressions, Bulletin of the Mexican Math-ematical Society 15(1) (2009), 23-36.

[3] E. Kılı¸c, Y.T. Uluta¸s and N. ¨Om¨ur, Formulas for weighted binomial sums with the powers of terms of binary recurrences, Miskolc Math. Notes, 13(1) (2012), 53-65. [4] E. Kılı¸c, N. ¨Om¨ur, and Y. Uluta¸s, Alternating sums of the powers of Fibonacci and

Lucas numbers, Miskolc Math. Notes 12 (1) (2011), 87-103.

[5] E. Kılı¸c and N. ¨Om¨ur, Some weighted sums of products of Lucas sequences, Integers, 2013, #A27.

[6] E. Kılı¸c, N. ¨Om¨ur and S. Koparal, On alternating weighted binomial sums with falling factorials, accepted in Bull. Math. Analysis and Appl.

[7] M. Khan and H. Kwong, Some binomial identities associated with the generalized natural number sequence, The Fibonacci Quarterly 49(1) (2011) 57–65.

[8] H. Prodinger, On a sum of Melham and its variants, The Fibonacci Quarterly, 46-47(3) (2008-2009), 207-215.

[9] M. Wiemann and C. Cooper, Divisibility of an F L type convolution. Applications of Fibonacci Numbers, 9 (2004), 267-287.

[10] S. Vajda, Fibonacci & Lucas numbers, and the golden section, John Wiley &Sons, Inc., New York, 1989.

TOBB Economics and Technology University, Mathematics Department 06560 Sogutozu Ankara Turkey

Kocaeli University Department of Mathematics 41380 ˙Izmit Kocaeli Turkey E-mail address: neseomur@kocaeli.edu.tr

Kocaeli University Department of Mathematics 41380 ˙Izmit Kocaeli Turkey E-mail address: sibel.koparal@kocaeli.edu.tr

Referanslar

Benzer Belgeler

n this paper we described a nonrectangular multiresolution wavelet representation for 2-D sig- nals and an image coding method which can com- press both quincunx and

Varoluşçu yaklaşım bireyin kendi kendini sorgulayarak doğrulama süreci üzerine yoğunlaşmaktadır. Seçim yapma kaygısıyla karşılaşınca otantik olabilmek

İlk aşamada, 1900-1950 yılları arasında toplumsal ve kültürel yapı, kadının toplumsal konumu, gelişen endüstri, teknolojik yenilikler, sanat akımları ve tasarım

Ulaşılan bi- reylerde; ölüm, iskemik veya hemorajik serebrovaskü- ler olay (svo), dekompanse kalp yetersizliği, akut koro- ner sendrom, hipertansif kriz, kardiyak aritmi,

6 Bu nedenle çalışmamızda, solunum döngüsü sırasında RT planlama amacıyla BT- simülatörde alınan görüntülerdeki CC tümör konumunun Dinamik MR

and Yükler A.I., “Influence of tool geometry and process parameters on macrostructure and static strength in friction stir spot welded polyethylene sheets”, Materials

The Effects of Densification and Heat Post-Treatment on Hardness and Morphological Properties of Wood Materials Mehmet Budakçı,a,* Hüseyin Pelit,a Abdullah Sönmez,b and Mustafa